Theoretical and Empirical Studies of Producer Cooperatives: Will Ever the Twain Meet? - Bonin, John P.; Jones, Derek C.; Putterman, Louis (Journal of Economic Literature, 1993)
The authors are grateful to Avner Ben-Ner, Jacques Defourny, Saul Estrin, Felix FitzRoy, Barbara Lee, Bentley MacLeod, Egon Neuberger, Jeffrey Pliskin, Stephen C. Smith, and three anonymous referees for comments on various drafts of this paper. Jones acknowledges with gratitude thefinancial assistance of the National Science Foundation (Grant # 9010591). Of course, all remaining errors and any omissions are entirely the responsibility of the authors.